Analisis Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas pada PT. Kereta Api Indonesia (Persero) Divre I Sumatera Utara - Khairul Hasanah; Hendra Harmain; Khairina Tambunan (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to find out about how the accounting information system for cash receipts and disbursements at PT. Kereta Api Indonesia (Persero) Divre I North Sumatra and to find out how the process of recording the accounting information system for cash receipts and disbursements at PT. Indonesian Railways (Persero) Divre I North Sumatra. The method used in this research is a descriptive qualitative research method. The data collection techniques used were observation, interviews and documentation. The recording system used at PT. Kereta Api Indonesia (Persero) Divre I North Sumatra uses the SAP (System Application and Processing) application. The SAP system itself has many advantages, both in terms of financial reports which are automatically separated so there is no need to separate financial reports manually. Procedure for Recording PT Cash Receipts. Kereta Api Indonesia has been running well in accordance with the company’s general cash receipts system. Source of cash receipts PT. KAI Head Office obtained from providing services from selling train tickets and renting fixed assets. However, there are obstacles in this procedure which have not been implemented optimally, giving rise to differences in bank accounts and in evidence of Cash Receipt Analysis due to recording errors that occurred in the PT accounting unit. KAI. PT. Cash Disbursement Recording Procedure. If seen from its implementation, Indonesian Railways is in accordance with the cash disbursement system and is running well. PT cash disbursements. KAI Head Office is used to finance the company’s operational activities. However, there are obstacles that occur during the recording process, in this case not all transactions received at the accounting unit are recorded regularly/daily so that recording errors and calculation differences still occur.